ENHANCING ACADEMIC COMMUNICATION SKILLS THROUGH CLASSROOM INTERACTION: A CASE STUDY OF SECONDARY SCHOOLS IN THE TAHOUA REGION OF NIGER - TCHAGNONHOU, Dèkandé Sylvestre; ZOUNHIN TOBOULA, Coffi Martinien; HOUNYETIN, Claude (My University, 2023)
This study examined how student participation affects their effectiveness in classroom communication. Despite completing seven years of secondary school, Tahoua’s Faculty of Education students demonstrated low proficiency in English and French. The study used various research methods to identify the root causes, including classroom observations, semi-structured teacher interviews, a student survey, and a randomized controlled trial. The data obtained from qualitative and quantitative sources were analyzed using inductive thematic analysis and descriptive and inferential statistics. The study involved classroom observations in both English and French language settings, with the experiment dividing students (n=1391) into two groups: one receiving standard instruction and the other receiving interactive instruction. The findings from the three-month experiment underscore the critical role of classroom engagement in academic communication. Specifically, the experimental group exhibited enhanced oral communication skills compared to the control group. Overall, the research underscores the benefits of interactive teaching tactics in improving students’ ability to express themselves in class.
Keywords: Academic communication skills; Tahoua region of Niger; Interactive teaching tactics; Secondary schools; Classroom interaction